The determination of quality of healthy indicators in swimming pools in Gorgan - MH.Mehdinezad (M.Sc) (مجله دانشگاه علوم پزشکی گرگان, 2003)
Background & Objective: Swimming pools are the most important sports field. The swimming effect on body and mental human health. The health, and disinfection of pools help to protect swimmers otherwise it can transfer agent of disease such as conjunctivitis-dermatit-athletes feet and parasitic in swimmers. The main purpose of this study is to survey the quality of health indicators in swimming pools and matching them with present standard in the Gorgan. Materials & Methods: This is a descriptive and cross-sectional study. It has performed on all of the swimming pool in summer season in Gorgan. In this study, general characteristics had determined by interview method and the parameters such as pH, turbidity, residual chlorine, Coliform bacteria, E.coli, Streptococcus Fecalis and Pseudomonas Aerogenosa determined in the laboratory. The sampling of water was performed every 10 days at 14-16 PM. The residual chlorine and pH determined in the field and the other parameters determined in the laboratory. Results: This research showed that pH>8 in 66.6% of samples and the amount of Coliform, E.coli and Streptococcus Fecalis were not at upper limit of standard, but the Pseudomonas Aerogenosa is more than limit of standard in 58.3% of samples. The residual chlorine was more limit of standard in 61.1% of samples and the amount of residual chlorine was according to limit of standard in Kiani and women’s pools. Conclusion: The lack of chlorinator system-inadequate of water treatment system and lack of knowledge pool’s incumbent cause that pH and residual chlorine were undesirable at most of the time. Additionally bacterial pollution confirms above subjects. So it is recommend that extensive research to be done on relationship between bacterial pollution and prevalence of disease in swimming pools.